2009
DOI: 10.5034/inquiryjrnl_46.03.339
|View full text |Cite
|
Sign up to set email alerts
|

Line Authority for Nurse Staffing and Costs for Acute Inpatient Care

Abstract: There is little empirical evidence evaluating the effects of recent, widespread changes in nurse executive roles and nursing management structures on the costs of patient care. This retrospective cross-sectional study examined the relationship between line authority for nurse staffing and patient care costs (total, nursing, and non-nursing cost) using data from 124 Department of Veterans Affairs (VA) medical centers. After controlling for patient, facility, and market characteristics, nursing line authority wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…9,13 Using VHA administrative databases, we identified all admissions (n = 144,918) to 325 acute medical/surgical units (ie, step-down, telemetry, medical, surgical, and mixed medical/surgical units) at 131 VA medical centers (VAMCs). At the facility level, we excluded 1 facility that was outside of a health service area (HSA) (2743 admissions), which meant that we could not associate the facility with market level characteristics ( Fig.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…9,13 Using VHA administrative databases, we identified all admissions (n = 144,918) to 325 acute medical/surgical units (ie, step-down, telemetry, medical, surgical, and mixed medical/surgical units) at 131 VA medical centers (VAMCs). At the facility level, we excluded 1 facility that was outside of a health service area (HSA) (2743 admissions), which meant that we could not associate the facility with market level characteristics ( Fig.…”
Section: Samplementioning
confidence: 99%
“…The VHA facility complexity grouping is based on empirical analysis of factors contributing to medical center complexity, including the number of patients seen at each VAMC, level of intensive care, patient risk measured by Medicare Relative Risk score, the number of resident slots, Herfindahl Index for resident slots, average research dollars per number of person seen, and the number of physician specialists per number of person seen. 9,13,21,22 Facility case mix was constructed from the 2002 VHA patient level Diagnostic Cost Group (DCG) relative risk score. 23,24 Hospital technology level was measured using the Saidin Index, 25 indicating whether a facility is capable of performing angioplasty procedure, cardiac catheterization, or open heart surgery, or had a trauma center.…”
Section: Measures and Sources Of Datamentioning
confidence: 99%
“…There are at least three nursing organizational models found in the literature: tasks-based model, in which tasks are assigned according to the training level of each nurse; a nursing team-based model, in which a group of patients is assigned to a nursing team heterogeneous in training and tasks are distributed among members, but the responsibility relies within the entire team; and a patient-centered care model, in which patients are assigned to one nurse who is responsible for their care during their hospital stay. Research conducted in developed countries (US, England, and Norway) shows that the patient-centered care model has a positive impact on the health status of hospitalized patients [5,10] , but the model is still controversial in relation to cost-effectiveness and the feasibility of making timely decisions about employee assignments [5,6] . Staff-assignment for all hospital services is one of the main responsibilities of nursing service heads and supervisors; however, this activity is becoming much more difficult to perform due to the world-wide nursing shortage [23,24] , which is also true for Peru and Mexico [17-19, 25, 26] as shown in our results.…”
Section: Discussionmentioning
confidence: 99%
“…One initiative proposes that instead of having a nursing management based on division of labor under rigid organizational structures it should be based on teamwork or patient-centered care [3] . Although evidence shows that patient-centered care improves nursing quality care and reduces costs [4,5] ; there is debate about the effectiveness of this model in relation to hospitalization costs and timely availability of nurse staffing in every hospital room [6] . Research conducted in Nordic countries indicates that nurse supervisors experience a high level of stress [7] , but research also found that nursing management has a positive impact on nurses that provide direct patient care.…”
mentioning
confidence: 99%
“…Cuando un entorno es positivo y saludable para el personal de enfermería, con alta probabilidad puede serlo para el resto de profesionales y para el usuario, lo que crea condiciones excelentes y un adecuado clima organizacional e institucional 3 para la mejora de la atención sanitaria 4 : reducen la morbimortalidad, las complicaciones no deseadas, las infecciones y los eventos adversos [5][6][7] , así como los costes de los procesos y gastos administrativos 8 ; al mismo tiempo, aumenta la satisfacción del paciente 3 . Estos resultados parecen estar basados, según la American Nurses Credentialing Center 9 , en determinados factores o dimensiones clave: empoderamiento estructural del personal de enfermería; práctica profesional ejemplar; incorporación de nuevos conocimientos a la práctica, mejoras e innovación, y liderazgo transformacional.…”
unclassified